Project management office effectiveness determinants in the UAE residential property toward stakeholders' satisfaction - Alblooshi, Saleh Salem (2024)
The residential property industry is attempting to find new strategies and instruments to improve the implementation of its projects. Among these instruments were those for project quality and Project management office effectiveness, which are dynamic and continuously changing aspects of the project landscape. These two factors help in improving the low internal stakeholder satisfaction reported within the residential property sector in the UAE. The low internal stakeholders' satisfaction has reduced the attractiveness of the residential property industry in the UAE. This study aims to investigate the role of project quality pillars such as project quality performance, project reliability, project aesthetics, project tangibility, and project assurance toward property internal stakeholder satisfaction through the mediation role of project management office effectiveness in the UAE residential property industry. The cross-sectional time horizon was used to collect the data from 309 internal stakeholders represented by managers from the UAE residential property companies. This study employed the structural equation modelling method for analysing the data collected. The finding of this study indicates that two pillars of project quality, project quality performance and project quality assurance, significantly impact internal stakeholders’ satisfaction. Also, the project management office's effectiveness was found to have a significant mediating role in the relationship between project quality aesthetics and project quality assurance with the stakeholders' satisfaction. This study contributes to the SERVQUAL model by exploring two additional pillars that replace two original factors from the model: responsiveness and empathy: project quality performance and project aesthetics, which are found to significantly affect the internal stakeholders' satisfaction through the project management office's effectiveness. This study could affect the project quality and the satisfaction of internal property stakeholders. Project quality activities should be focused on moral principles and ethical philosophy and values, and these activities should result in the creation of successful decision-making skills among individuals within the company. Further attention should be paid to the cooperative management system, which results in the achievement of the organisational goal of mutual benefit and cooperation. Lastly, it is important for employees to be involved in making decisions and for their honesty to be recognised by the company.